O objeto na comunicação dos lugares - Arnas, Teglis Pepe Barbalho (2007)
Human interactions in their social areas occur in a setting which changes according to interpersonal relationships and social ties. This place can be represented by environments characterized by a system of objects which emerges as an efficient element of communication. These living environments and, consequently the communicative relationships with men, have been suffering changes along history, mainly after the development of new technologies at the end of the 20th century and the beginning of the 21st Century. Environmental design may interfere in the communicative relationships and influence individuals and social groups, determining their cultural identities. This study aims to perceive and analyze to what extent an environmental design might be able to interfere in communicative relationships, pursuing the ability to generate information from the perception and analysis of the transition from the culture of the object to the culture of the system of objects. The study of the languages which set (different) environments becomes relevant to a better understanding of relationships, influencing the valuation of human beings, which may contribute to the optimization of life. The theoretical semiotic support in connection with the System of Objects of Jean Baudrillard allows the research to reach the recognition of environmental languages and to explain the signs that compose them. The categories of spatiality, visuality, communicability and perceptibility, in relation to these environmental systems, enable to capture the manner of representing environments, and consequently to make a judgment on this experience